The Study on Plant and Animal Sources Resemble Body Parts in Kitchen Chemistry - Sathiyaseelan, V.; Balayogan, T. (Institute of Indigenous Medicine University of Colombo, Rajagiriya Sri Lanka, 2016)
Plant and animal sources have clues in their shapes & forms and actions that tell what their purposes are. There were fruits and vegetables out there that are good for a certain part of human body and look like that body part as well. Chemical constituents in this food help to develop structure and function of some particular organs. These information. was gathered from text books of Siddha, other western text books and as well as in internet. 50 plants were taken for research and among them, there are 34 plants sources and 3 animal sources were identified that they have connection with human organs. Among 34, there are 9 plant and 2 animal sources are used to maintain the health of genitor urinary system, 5 for cardiovascular System, 2 for central nervous system, 2 for gastrointestinal Track, 3 for skeletal system, 2 for eye, 1 for ear, 1 for teeth and 2 to protect the normal function of cells from malignancy. According to this study some plants which have same morphological feature of human organs help to strengthen the particular organ. Food is a medicine and medicine is food. According to that, some sources act as rejuvenation to our body. In Siddha aspect these foods help to grow and maintain the health of 7 Udall kattu. Identification of these foods will help us to keep the particular organs healthier and to cure the disease.
Keywords: Plants; Animals; Purposes; Organs; Chemical constituents